2018
DOI: 10.1103/physrevb.97.224514
|View full text |Cite
|
Sign up to set email alerts
|

Devil's staircases in the IV characteristics of superconductor/ferromagnet/superconductor Josephson junctions

Abstract: We study the effect of coupling between the superconducting current and magnetization in the superconductor/ferromagnet/superconductor Josephson junction under an applied circularly polarized magnetic field. Manifestation of ferromagnetic resonance in the frequency dependence of the amplitude of the magnetization and the average critical current density is demonstrated. The IV characteristics show subharmonic steps that form devil's staircases, following a continued fraction algorithm. The origin of the found … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…In case of external electromagnetic field which leads to the additional electric current I ac = A sin Ωt, the width of the Shapiro step is proportional to ∝ J n (A/Ω), where J n is the Bessel function of first kind. The preliminary results (not presented here) show that the width of the Shapiro-like steps under external magnetic field has a more complex frequency dependence 20 . This question will be discussed in detail somewhere else.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In case of external electromagnetic field which leads to the additional electric current I ac = A sin Ωt, the width of the Shapiro step is proportional to ∝ J n (A/Ω), where J n is the Bessel function of first kind. The preliminary results (not presented here) show that the width of the Shapiro-like steps under external magnetic field has a more complex frequency dependence 20 . This question will be discussed in detail somewhere else.…”
Section: Resultsmentioning
confidence: 68%
“…In Ref. [20] we show that taking into account the effective field due to Josepshon energy and at FMR, additional subharmonic current steps appear in the IV-characteristic for overdamped SFS junction with spin wave excitations (magnons). It is found that the position of the current steps in the IV-characteristics form devil's staircase structure which follows continued fraction formula 20 .…”
Section: Introductionmentioning
confidence: 99%
“…В этой модели расчеты могут быть выполнены весьма точно, что позволяет разобраться в деталях происходящих процессов. Поэтому процессы в длинных джозефсоновских контактах анализируются в значительном числе работ [7][8][9].…”
Section: Introductionunclassified
“…Она может быть решена весьма точно, что позволяет понять различные детали происходящих процессов. Поэтому исследованиям процессов в длинных джозефсоновских контактах посвящено значительное число работ [7][8][9].…”
Section: Introductionunclassified